Unraveling the roles of endoplasmic reticulum-associated degradation in metabolic disorders - Luo, Hui; Jiao, Qibin; Shen, Chuanbin; Shao, Chenyi; Xie, Jinyan; Chen, Yue; Feng, Xinglin; Zhang, Xingwei (Frontiers in Endocrinology, 2023)
Misfolded proteins retained in the endoplasmic reticulum cause many human diseases. ER-associated degradation (ERAD) is one of the protein quality and quantity control system located at ER, which is responsible for translocating the misfolded proteins or properly folded but excess proteins out of the ER for proteasomal degradation. Recent studies have revealed that mice with ERAD deficiency in specific cell types exhibit impaired metabolism homeostasis and metabolic diseases. Here, we highlight the ERAD physiological functions in metabolic disorders in a substrate-dependent and cell type-specific manner.